Therapeutic Community for Victims of Narcotics Abuse at the Mutiara Abadi Binjai Rehabilitation Center, Bandar Senembah Village, Binjai Barat District-Binjai City (Analysis of PP. Number 25 of 2011 and Maqashid Al-Syari'ah) - Hamdan Mubarok; Zulkarnain Zulkarnain; Hafsah Hafsah (Universitas Muhammadiyah Sumatera Utara, 2023)
This study aims: (1) To find out PP No.25 of 2011 regulates rehabilitation in the Therapeutic Community approach, (2) To find out Therapeutic Community at the Mutiara Abadi Binjai Rehabilitation Center based on PP No.25 of 2011, (3). To find out the Therapeutic Community at the Mutiara Abadi Binjai Rehabilitation Center in terms of Maqashid Al-Syari'ah. This research is a field research that uses empirical juridical methods. This research approach is statutory, case approach, conceptual approach. The sources of this research are primary data sources obtained directly from the original sources in the form of interviews, opinion polls from individuals or groups (people) and secondary data obtained through intermediary media or indirectly in the form of books, notes, existing evidence, or archives, both published and unpublished. The results of this study are the results of assessments and Ministerial Regulations